Actual quantitative attachment gain secondary to use of autologous platelet concentrates in the treatment of intrabony defects: A meta-analysis - Om Kumar Nemichand Baghele; Vrushali Madhavrao Kathole; Amarpreet Kaur Jasbirsingh Tuteja; Trupti Gajendra Giri (Wolters Kluwer Medknow Publications, 2019)
Background: There are no authoritative meta-analyses and no clear quantitative assessments available estimating effects of open flap debridement (OFD) combined with platelet-rich fibrin (PRF) or platelet-rich plasma (PRP) over and above that of OFD. This study evaluated the actual quantitative mean gain for various clinical (clinical attachment level [CAL], probing pocket depth [PPD] and gingival marginal level [GML]) and radiographic (intrabony defect depth [IBD]) parameters of Platelet Concentrates- PCs (PRP/PRF) as sole grafting material along with OFD and OFD alone in the treatment of intrabony defects. Materials and Methods: A detailed electronic search was carried out in PUBMED/MEDLINE, COCHRANE, EBSCOHOST, and Google Scholar databases by unifying related search terms with additional hand searches in select specialty journals up to May 2017. The eligibility criteria included human randomized clinical trials, either of a parallel group or a split-mouth design with follow-up period of at least 6 months. Periodontal intrabony defects with radiographic IBD ≥3 mm with corresponding CAL ≥5 mm were included. For the meta-analysis, the inverse variance method was used in fixed- or random-effect models. Results: Actual quantitative mean gains were calculated for OFD with PRF/PRP (CAL = 1.1 mm, IBD = 1.68 mm, PPD = 0.97 mm and GML = 0.48 mm) over and above that of OFD alone. Conclusion: Because of very high heterogeneity, the results may not be dependable. Apart from gains in radiographic bone fill, all other periodontal clinical parameters showed negligible gains. Using PRF technologies in periodontal intrabony defects may not be of great clinical significance over and above that of OFD alone, the effect sizes are also not large enough.